HDAC5 Controls MEF2C‐Driven Sclerostin Expression in Osteocytes. (25th February 2015) - Wein, Marc N; Spatz, Jordan; Nishimori, Shigeki; Doench, John; Root, David; Babij, Philip; Nagano, Kenichi; Baron, Roland; Brooks, Daniel; Bouxsein, Mary; Pajevic, Paola Divieti; Kronenberg, Henry M
ABSTRACT: Osteocytes secrete paracrine factors that regulate the balance between bone formation and destruction. Among these molecules, sclerostin (encoded by the gene SOST) inhibits osteoblastic bone formation and is an osteoporosis drug target. The molecular mechanisms underlying SOST expression remain largely unexplored. Here, we report that histone deacetylase 5 (HDAC5) negatively regulates sclerostin levels in osteocytes in vitro and in vivo. HDAC5 shRNA increases, whereas HDAC5 overexpression decreases SOST expression in the novel murine Ocy454 osteocytic cell line. HDAC5 knockout mice show increased levels of SOST mRNA, more sclerostin‐positive osteocytes, decreased Wnt activity, low trabecular bone density, and reduced bone formation by osteoblasts. In osteocytes, HDAC5 binds and inhibits the function of MEF2C, a crucial transcription factor for SOST expression. Using chromatin immunoprecipitation, we have mapped endogenous MEF2C binding in the SOST gene to a distal intergenic enhancer 45 kB downstream from the transcription start site. HDAC5 deficiency increases SOST enhancer MEF2C chromatin association and H3K27 acetylation and decreases recruitment of corepressors NCoR and HDAC3. HDAC5 associates with and regulates the transcriptional activity of this enhancer, suggesting direct regulation of SOST gene expression by HDAC5 in osteocytes. Finally, increased sclerostin production achieved by HDAC5 shRNA is abrogated by simultaneous knockdown of MEF2C, indicating that MEF2C is a major target of HDAC5 in osteocytes. © 2014 American Society for Bone and Mineral Research.